The efficacy of pericapsular nerve group block for postoperative analgesia in patients undergoing hip surgery: A systematic review and meta-analysis of randomized controlled trials - Yu, Liang; Shen, Xiaojuan; Liu, He (Frontiers in Medicine, 2023)
Background As an optional regional anesthesia approach, pericapsular nerve group (PENG) block has been successfully utilized to manage pain for hip surgeries without affecting motor function. The present meta-analysis aimed to verify the efficacy of PENG block for postoperative analgesia in patients undergoing hip surgery. Methods A total of 497 academic articles were identified after a systematic search in the databases of PubMed, Embase, Web of Science, and Cochrane Library up to 25 August 2022. The primary outcome was postoperative 24-h morphine consumption. Secondary outcomes included the time of the first request for rescue analgesia, static and dynamic pain scores 6 and 24 h after surgery, and incidence of postoperative nausea and vomiting (PONV). We calculated mean differences (MDs) with 95% confidence intervals (CIs) for postoperative 24-h morphine consumption, time of the first request for rescue analgesia, static and dynamic pain scores 6 and 24 h after surgery, and odds ratios (ORs) with 95% CIs for incidence of PONV. The chi-square test was used for heterogeneity analysis, and heterogeneity was assessed by I2. Statistical analysis was performed using Review Manager 5.4. Results Numerous electronic databases were searched, and finally, nine studies were identified. There was no significant difference in morphine consumption during the postoperative 24 h [MD: −2.57, 95% CI: (−5.42, 0.27), P = 0.08] and the time of the first request for rescue analgesia [MD: 1.79, 95% CI: (−1.06, 4.64), P = 0.22] between the PENG block and control groups. PENG block did not reveal a significant difference in 6 h [MD: −0.17, 95% CI: (−0.92, 0.57), P = 0.65] [MD: −0.69, 95% CI: (−1.58, 0.21), P = 0.13] and 24 h [MD: −0.25, 95% CI: (−1.54, 1.05), P = 0.71], [MD: 0.05, 95% CI: (−0.84, 0.93), P = 0.91] static and dynamic pain scores compared with other nerve block methods. Moreover, the two groups have a similar risk of PONV (OR: 1.29, 95% CI = 0.53–3.10, P = 0.57). Conclusion This review shows that PENG block can act as an alternative multimodal analgesia for hip surgery, and compared with the other kinds of nerve block, there was no significant difference in the postoperative analgesic effect of PENG block. Systematic review registration Supplementary Datasheet 1, identifier: CRD 42022356496.